Genetic and morpho-physiological differentiation in a limpet population across an intertidal gradient - Nuñez, Jesus Dario (2018)
Marine organism adaptive capacity to different environmental conditions is a research priority to understand what conditions are important in structuring the spatial distribution of natural populations. In this context, this study evaluates whether potential differences in Siphonaria lessonii morphology (size and shell shape) and physiology (water loss regulation) at different shore heights are linked to genetically distinguishable individuals. To achieve this goal, we compared size-frequency distribution, morphometric, and genetic data (ISSR-PCR technique) of S. lessonii from the upper, middle and lower shore. We complemented these field samplings with laboratory experiments on water loss and mortality. Genetic analysis showed different genetic composition for individuals from the upper and lower shore. This pattern was accompanied by morpho-physiological variations: the upper shore had fewer small limpets, lower shell shape dispersion (with a morphotype characterized by a higher shell), and less water loss and mortality related to air exposure than the lower shore. The results reported herein support the idea that the extreme and unpredictable conditions of the upper shore may impose strong selection pressure on its inhabitants, leading to considerable morpho-physiological differentiation consistent with different genetic composition. This probably plays an important role in structuring the spatial distribution of natural S. lessonii populations with a possible effect on size-structure distribution.